Quality indicators for collaborative care networks in persistent somatic symptoms and functional disorders: a modified delphi study - Nick Mamo; Lineke M. Tak; Manouk A. W. van de Klundert; Tim C. Olde Hartman; Judith G. M. Rosmalen; Denise J. C. Hanssen (BMC, 2024)
Abstract Background Care for persistent somatic symptoms and functional disorders (PSS/FD) is often fragmented. Collaborative care networks (CCNs) may improve care quality for PSS/FD. Effectiveness likely depends on their functioning, but we lack a straightforward quality evaluation system. We therefore aimed to develop quality indicators to evaluate CCNs for PSS/FD. Method Using an online three-round modified Delphi process, an expert panel provided, selected and ranked quality indicators for CCNs in PSS/FD. Recruited experts were diverse healthcare professionals with relevant experience in PSS/FD care in the Netherlands. Results The expert panel consisted of 86 professionals representing 15 disciplines, most commonly physiotherapists, psychologists and medical specialists. 58% had more than 10 years experience in PSS/FD care. Round one resulted in 994 quotations, which resulted in 46 unique quality indicators. These were prioritised in round two and ranked in round three by the panel, resulting in a final top ten. The top three indicators were: "shared vision of care for PSS/FD", "pathways tailored to the individual patient", and "sufficiently-experienced caregivers for PSS/FD". Conclusions The identified quality indicators to evaluate CCNs in the field of PSS/FD can be implemented in clinical practice and may be useful in improving services and when assessing effectiveness.